de Broglie's eqn. proof goes this way:---(adsbygoogle = window.adsbygoogle || []).push({});

E = m*c^{2}

E = h*c/L (L - Wavelength)

the they are equated -

m*c^{2}=h*c/L

=> L=h/(m*c)

But in E=m*c^2, m is the mass lost by some body to give energy E not mass of photon,

then why do we consider m mass of photon ??

By considering that we find equivalent eqn.--

L=h/(m*v)

for any mass m.

Isn't that wrong??

**Physics Forums - The Fusion of Science and Community**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# De-Broglie equation proof

Can you offer guidance or do you also need help?

Draft saved
Draft deleted

Loading...

Similar Threads for Broglie equation proof | Date |
---|---|

De Broglie Equations | May 23, 2013 |

De broglie wave equation | Mar 12, 2013 |

Showing that the Schrödinger equation implies the de Broglie relation when PE=0 | Nov 1, 2012 |

Struggling to understand the de Broglie equation | Apr 25, 2011 |

Proof of de broglie equation? | Mar 10, 2009 |

**Physics Forums - The Fusion of Science and Community**